2014
DOI: 10.1083/jcb.201402104
|View full text |Cite
|
Sign up to set email alerts
|

PINK1 phosphorylates ubiquitin to activate Parkin E3 ubiquitin ligase activity

Abstract: PINK1 phosphorylates ubiquitin, which then binds to Parkin and activates its E3 ligase activity, leading to induction of selective autophagy of damaged mitochondria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
985
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,102 publications
(1,018 citation statements)
references
References 42 publications
28
985
2
3
Order By: Relevance
“…Rather, this step optimizes parkin for Ubl phosphorylation and E2~Ub engagement (Fig 6B; Kumar et al , 2015; Ordureau et al , 2015). It is well established that phosphorylation of the Ubl domain following pUb recruitment significantly increases its ubiquitination activity (Kondapalli et al , 2012; Shiba‐Fukushima et al , 2012; Kane et al , 2014; Kazlauskaite et al , 2014; Koyano et al , 2014). Current NMR dynamics analysis of R0RBR parkin:pUb as a proxy for this state shows the IBR domain is considerably less mobile due to engagement with pUb although a large stretch of the tether region remains mobile, an observation not obvious from current crystal structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, this step optimizes parkin for Ubl phosphorylation and E2~Ub engagement (Fig 6B; Kumar et al , 2015; Ordureau et al , 2015). It is well established that phosphorylation of the Ubl domain following pUb recruitment significantly increases its ubiquitination activity (Kondapalli et al , 2012; Shiba‐Fukushima et al , 2012; Kane et al , 2014; Kazlauskaite et al , 2014; Koyano et al , 2014). Current NMR dynamics analysis of R0RBR parkin:pUb as a proxy for this state shows the IBR domain is considerably less mobile due to engagement with pUb although a large stretch of the tether region remains mobile, an observation not obvious from current crystal structures.…”
Section: Discussionmentioning
confidence: 99%
“…This in turn helps recruit parkin to the membrane through binding of pUb to the RING1–IBR region of the E3 ligase (Sauvé et al , 2015; Wauer et al , 2015; Kumar et al , 2017) and subsequent phosphorylation of parkin's Ubl (pUbl) domain (Ordureau et al , 2014). These two events greatly stimulate ubiquitination activity (Kondapalli et al , 2012; Shiba‐Fukushima et al , 2012; Kane et al , 2014; Kazlauskaite et al , 2014; Koyano et al , 2014) through an allosteric displacement mechanism of the pUbl domain from parkin (Kumar et al , 2015; Sauvé et al , 2015). What is less clear is how parkin positions the E2~Ub conjugate to enable transfer of the Ub molecule to the RING2(Rcat) domain as a necessary step for catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…In healthy mitochondria PINK1 is subject to constant turnover; cleavage of its mitochondrial targeting sequence by the mitochondria intermembrane space protease PARL reveals a destabilizing N-terminal residue that targets PINK for proteasomal degradation 7,8 . Disruption of mitochondrial function causes an accumulation of PINK1 on the mitochondrial outer membrane where it phosphorylates ubiquitin and Parkin leading to activation of the PARKIN E3 ubiquitin ligase at the mitochondria [9][10][11] . Parkin recruitment to mitochondria requires mitofusin 2 (MFN2) in some settings 12,13 but is dispensible in others 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In a feed-forward mechanism, Parkin ubiquitinates mitochondrial substrates that, in turn, leads to more PINK1 substrate phosphorylation and Parkin activity. Ubiquitinated mitochondria are targeted for autophagy following recognition by specific ubiquitin binding adaptor proteins 9 . Importantly, experimentally induced PINK1/Parkin-mediated mitophagy can reduce mitochondrial levels to below the level of detection, thereby opening its use as an experimental tool to study mitochondrial function 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…By using a combination of proteomics screen, Phos-tag-based gel retardation assays and in vitro kinase assays, three different groups found that PINK1 directly phosphorylates ubiquitin [7][8][9]. Mass spectrometry and mutagenesis assays showed that phosphorylation occurs uniquely on serine 65, a residue shared by both ubiquitin and the Parkin Ubl.…”
mentioning
confidence: 99%